Effect of UV‐irradiation intensity on graft polymerization of 2‐methacryloyloxyethyl phosphorylcholine on orthopedic bearing substrate. Issue 9 (7th October 2013) - Kyomoto, Masayuki; Moro, Toru; Yamane, Shihori; Hashimoto, Masami; Takatori, Yoshio; Ishihara, Kazuhiko
Abstract Photoinduced grafting of 2‐methacryloyloxyethyl phosphorylcholine (MPC) onto cross‐linked polyethylene (CLPE) was investigated for its ability to reduce the wear of orthopedic bearings. We investigated the effect of UV‐irradiation intensity on the extent of poly(MPC) (PMPC) grafting, and found that it increased with increasing intensity up to 7.5 mW/cm2, and the remained fairly constant. It was found to be extremely important to carefully control the UV intensity, as at higher values, a PMPC gel formed via homopolymerization of the MPC, resulting in the formation of cracks at the interface of the PMPC layer and the CLPE substrate. When the CLPE was exposed to UV‐irradiation during the graft polymerization process, some of its physical and mechanical properties were slightly changed due to cross‐linking and scission effects in the surface region; however, the results of all of the tests exceed the lower limits of the ASTM standards. Modification of the CLPE surface with the hydrophilic PMPC layer increased lubrication to levels that match articular cartilage. The highly hydrated thin PMPC films mimicked the native cartilage extracellular matrix that covers synovial joint surface, acting as an extremely efficient lubricant, and providing high‐wear resistance. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3012–3023, 2014.